Dynamics of Multiculturalism in Contemporary Society: Challenges and Opportunities - sanusi, Aan (Universitas Islam Raden Rahmat Malang, 2024)
This discussion aims to delve deeper into the Challenges and Opportunities of Multicultural Dynamics in Contemporary Society. The purpose is to gain a clear understanding of the challenges and opportunities in the dynamics of multiculturalism in contemporary society. This research is a type of library research, where data is derived from literature related to the research object and then analyzed for its content. This study asserts that multiculturalism refers to the existence and interaction among various cultural or ethnic groups within a society. In contemporary society, the challenges and opportunities of multiculturalism can be complex and varied depending on the context. Some of the challenges include: conflicts of values and beliefs, lack of understanding, social isolation, policy conflicts, communication challenges, social and economic inequality, globalization and cultural homogenization, radicalization, and extremism. As for the opportunities, they include: innovation and creativity, economic growth, rich education, increased intercultural awareness, the strength of global collaboration, growth in tourism and the creative industry, increased tolerance and appreciation, and the strengthening of national identity.